2017
DOI: 10.18280/mmep.040102
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of functionally graded beams using a higher-order shear deformation theory

Abstract: This paper presents an analytical solution to the free vibration analysis of functionally graded beams by using a refined hyperbolic shear deformation theory in which the stretching effect is included. The modulus of elasticity of beams is assumed to vary according to a power law distribution in terms of the volume fractions of the constituents. Equations of motion are derived from Hamilton's principle and Navier-type analytical solutions for simply supported beams are compared with the existing solutions to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Based on the sensitivity of electronic nose gas recognition, the transient response information model of wireless sensor is established, and the gas eigenvalue and mixed gas are identified to realize the qualitative and quantitative analysis of gas [14]. The gas sensing mechanism based on wireless gas sensor involves many theories such as material surface morphology, gas sensing material microstructure and gas response dynamics [15][16]. The wireless sensor for gas recognition detects gas by the change in the resistance value of the gas after reaction on the surface of the semiconductor thin film.…”
Section: Dynamic Analysis Of Wireless Sensor Responsementioning
confidence: 99%
“…Based on the sensitivity of electronic nose gas recognition, the transient response information model of wireless sensor is established, and the gas eigenvalue and mixed gas are identified to realize the qualitative and quantitative analysis of gas [14]. The gas sensing mechanism based on wireless gas sensor involves many theories such as material surface morphology, gas sensing material microstructure and gas response dynamics [15][16]. The wireless sensor for gas recognition detects gas by the change in the resistance value of the gas after reaction on the surface of the semiconductor thin film.…”
Section: Dynamic Analysis Of Wireless Sensor Responsementioning
confidence: 99%
“…In brief, the optical passive non-thermal design is to utilize the difference between the thermal characteristics of optical materials, eliminate the influence of temperature through reasonable combination of different characteristic materials, and reasonably match the optical power distribution scheme of the materials, so that the defocus of the optical system resulting from the change in temperature offsets the defocus of the the mechanical tube resulting from expanding with heat and contracting with cold, realizing the purpose of automatic temperature compensation. Strictly speaking, the non-thermal design of the optical system needs to meet the requirements of thermal elimination, achromatic aberration and optical power [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Optical Passivementioning
confidence: 99%
“…In a study by Zohra et al [20], the critical buckling temperatures and natural frequencies of beams with a thickness functional gradient were investigated, and it was observed that the effects of shear deformation on frequencies tend to be more significant when the beams become shorter (thicker). These effects were more evident for higher mode frequencies.…”
Section: Introductionmentioning
confidence: 99%